Kinerja Keuangan Pengaruhnya Terhadap Harga Saham - Hadi Saputro, Dian Festiana; Setyowati, Lilis (Universitas Dian Nuswantoro, 2023)
This study aims to determine the effect of financial performance consisting of the current ratio, return on equity, return on assets, price earning ratio, and net profit margin on stock prices in energy sector companies listed on the Indonesia Stock Exchange in 2020-2021. The sampling technique used purposive sampling method. The number of final samples obtained by a number of 91 companies that have met the criteria. Methods of data analysis using multiple linear regression analysis. The results showed that the current ratio has no significant effect on stock prices. Return on equity has no significant effect on stock prices. Return on assets has a significant effect on stock prices. Price Earning Ratio has a significant effect on stock prices. Net profit margin has a significant negative effect on stock prices.